Moving color : early film, mass culture, modernism - Yumibe, Joshua (Rutgers University Press, 2012)
Moving Color is the first book-length study of the beginnings of color cinema. It traces the legacy of color history from the beginning of the nineteenth century to the cinema of the early twentieth century and explores the implications of this genealogy on experimental and contemporary digital cinemas.
Keywords: Color cinematography -- History.; Colorization of motion pictures -- History.; Silent films -- History and criticism.; Colors in motion pictures.; Cinéma en couleurs -- Histoire.; Colorisation des films -- Histoire.; Films muets -- Histoire et critique.; Couleurs au cinéma.; ART -- Film & Video.; PHOTOGRAPHY -- Techniques -- Cinematography & Videography.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Color cinematography; Colorization of motion pictures; Colors in motion pictures; Silent films; Criticism, interpretation, etc.; History